Role of Amino Acid Oxidation in the Peroxyl Radical Mediated Inactivation of Glucose-6-Phosphate Dehydrogenase and 6-Phosphogluconate Dehydrogenase: Two Key Enzymes of the Pentose Phosphate Pathway - Arenas-Salinas, F (ELSEVIER SCIENCE INC, 2022)
Sin Resumen Disponible